A case study on Unimas pre-service teachers' help-seeking behaviour during teaching practice - Lee, Hui Hui (Universiti Malaysia Sarawak (UNIMAS), 2007)
This study reports the help-seeking behaviour among the 24 pre-service teachers in Unimas TESL programme, as to identify their behaviour in seeking help, whom they seek help and through which channels of communication that they used during the teaching practice. The interview and checklist are used to collect the intended data in this Study. From the finding, it stated that the pre-service teachers actually fend to seek help from their peer most frequent and often through the face-to-face communication to solve the problem they faced during reaching practice. Hence, this study, suggests that peer support is important during teaching practice and face-to-face communication should be encouraged as it is really an effective way to gain help from other.